The Effect of Work Opportunity Requirements Checklist (WORC) to Grade 12 Work Immersion Students - Norelyn H. Data; Shella Mae W. Pareja (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
The purpose of this study was to examine the effect of the Work Opportunity Requirements Checklist (WORC) for Grade 12 students who will undergo work immersion program to reduce failure by compensating for potential limits of human memory and attention; to ensure consistency and completeness in carrying out a task; to analyze the needs and special requirements for work immersion program; to help students stay more organized; assuring them they will not skip any important step in the process; to help move quickly; be more efficient, and save time. In this research process, researchers used the method of quantitative method. Data for the study were collected through a survey form. During the one-month implementation of the work immersion program, students were exposed to securing and preparing work immersion documents. After the data gathering, tabulation, evaluation, and analysis, the researchers concluded that the Work Opportunity Requirements Checklist (WORC) has improved students’ soft skills abilities such as self-management, self-motivation, decision making, time management, being responsible, goal setting, prioritizing, focus, attention to detail, and enhanced their retention skills. Furthermore, the students-participants had experienced success in organizing their work documents and minimizing mistakes in accomplishing the work immersion requirements, their organizational skills indeed are well in the progress.